An Unusual Grob–type C–C/C‐O Bond Cleavage of 5‐Acyl‐2, 3‐dihydro‐4H‐pyran‐4‐one Derivatives. Issue 5 (29th April 2016) - Ilangovan, Andivelu; Sakthivel, Palaniappan; Zipse, Hendrik
Abstract: A variety of 5‐aroyl/alkanoyl‐2, 3‐dihydro‐4 H ‐pyran‐4‐ones have been synthesised by reaction between acyclic β‐diketones and α, β‐unsaturated acyl chlorides in the presence of CaCl2 as catalyst. The reaction proceeds via domino C‐acylation/6π‐oxaelectrocyclization. The aryl‐substituted 2, 3‐dihydropyranones, on treatment with hydrazine hydrate, underwent an unusual, sequential, C−C and C−O bond cleavage via tandem nucleophilic 1, 2‐addition/Grob‐type fragmentation to provide 3, 5‐disubstituted 1 H ‐pyrazoles, under mild and metal free conditions. However, the corresponding alkyl‐substituted 2, 3‐dihydropyranones underwent only C−O bond cleavage to furnish 4‐acyl‐3, 5‐disubstituted‐1 H ‐pyrazoles. The reaction free energies have been calculated at the B3LYP/6‐31+G(d) level of theory for the formation of differently substituted pyrazoles. The value −215.0 kJ/mol, observed for overall reaction between diphenyl‐substituted DHP3 aa and 2 equiv. of hydrazine support the formation of ynoneIII intermediate and its subsequent cyclization to form diphenyl pyrazole7 aa . In the case of dialkyl‐substituted DHP3 pa nucleophilic attack at the C4 position is too unfavorable on thermochemical grounds. Abstract : Domino C‐acylation/6π‐oxaelectrocyclization protocol was employed for a wide‐scope synthesis of substituted 5‐acyl DHPs. The alkyl or aryl substituent present on 5‐acyl group was found to control the Grob‐type C−C/C−O fragmentation of 5‐acyl‐2, 3‐dihydro‐4H‐pyran‐4‐ones. This tandem C−C/C−O bond cleavage took place with just hydrazine, instead of the usually used strong inorganic bases. The reaction free energies have been calculated at the B3LYP/6‐31+G(d) level of theory for the formation of differently substituted pyrazoles.